2011
DOI: 10.1016/j.rbmo.2010.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Surgical procedure to conserve the uterus for future pregnancy in patients suffering from massive adenomyosis

Abstract: The treatment for severe adenomyosis has usually been hysterectomy, because there is no line of demarcation between diseased and normal tissue. Yet many such women wish to retain their uterus and some even wish to bear children. This report evaluates the efficacy of a new method of adenomyomectomy, where adenomyotic tissues are radically excised and the uterine wall is reconstructed by a triple-flap method, without overlapping suture lines, to prevent uterine rupture in subsequent pregnancies. This is a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
133
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 7 publications
1
133
2
5
Order By: Relevance
“…25,26 The present results show an increase in the incidence of intrauterine infection . [27][28][29][30] In the present study, there were no data to suggest that conservative surgery as a pretreatment for adenomyosis before pregnancy reduced the incidence of pregnancy complications. However, as the surgical techniques differed by facility, it is difficult to analyze the association between the pregnancy outcomes and the individual surgical techniques.…”
mentioning
confidence: 64%
“…25,26 The present results show an increase in the incidence of intrauterine infection . [27][28][29][30] In the present study, there were no data to suggest that conservative surgery as a pretreatment for adenomyosis before pregnancy reduced the incidence of pregnancy complications. However, as the surgical techniques differed by facility, it is difficult to analyze the association between the pregnancy outcomes and the individual surgical techniques.…”
mentioning
confidence: 64%
“…A new conservative technique to be employed in women with adenomyosis wishing to become pregnant has just been published (Osada et al, 2011). Indications for surgery were based on size and extent of lesions.…”
Section: Treatment Of Adenomyosis-associated Infertilitymentioning
confidence: 99%
“…A recent study by Osada et al (2011) reported 45 patients with large adenomyosis who had IVF treatment before attempting cytoreductive surgery. A total of 17 patients (37.8%) conceived, only to miscarry in the 1st trimester (longest 14 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Th e third and most recent case series (Osada et al 2011), included a prospective 104 patients over a 10-year period. Following surgery, 26 patients wished to conceive.…”
Section: Discussionmentioning
confidence: 99%